1. PARENTING STYLE AND SELF-IDENTITY AMONG SECONDARY SCHOOL STUDENTS - Mohd Rafidi, Nor Marina; Saibon, Jamalsafri; Ahmad Seliban, Ahmad Sharani (Journal of Islamic, Social, Economics and Development, 2024)
This study stands out for its innovative application of the Nominal Group Technique (NGT) to identify effective parenting styles for adolescent identity formation. By engaging with five parents of secondary school students, the study utilized structured discussions and voting to determine the most suitable parenting styles for fostering self-identity. The results compellingly indicate that authoritative parenting, characterized by a balanced approach of firmness and responsiveness, is strongly associated with the development of a clear and confident self-identity in adolescents. Parents who adopted this style reported higher levels of self-confidence and well-defined identities in their children compared to those who employed permissive or authoritarian approaches. These findings provide valuable empirical support for promoting authoritative parenting practices to nurture well-adjusted and confident adolescents. Future research should expand these findings by incorporating direct observational methods and engaging a more diverse participant demographic to enhance the generalizability of the results. This study is the first to employ NGT in identifying parenting styles linked to adolescent self-identity, highlighting its importance in understanding developmental pathways to support a stable society and strong individual identities.